2017
DOI: 10.1590/s1808-185120171601162774
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar Spinal Arthrodesis - Epidemiology and Costs

Abstract: Objective: To describe the epidemiology of patients with thoracolumbar spine fracture submitted to surgery at Hospital Cristo Redentor and the related costs. Methods: Prospective epidemiological study between July 2014 and August 2015 of patients with thoracolumbar spine fracture with indication of surgery. The variables analyzed were sex, age, cost of hospitalization, fractured levels, levels of arthrodesis, surgical site infection, UTI or BCP, spinal cord injury, etiology, length of stay, procedure time, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The present work showed that spine trauma mostly occurred in young males, corroborating previously published articles. [7][8][9]12,29 A study published in the same state found similar distribution by age and sex. 30 A progressive increase in rates of spine trauma was observed in patients aged over 65 years old; from 4.8% to 12.1%.…”
Section: Distribution By Age and Sexmentioning
confidence: 67%
See 1 more Smart Citation
“…The present work showed that spine trauma mostly occurred in young males, corroborating previously published articles. [7][8][9]12,29 A study published in the same state found similar distribution by age and sex. 30 A progressive increase in rates of spine trauma was observed in patients aged over 65 years old; from 4.8% to 12.1%.…”
Section: Distribution By Age and Sexmentioning
confidence: 67%
“…[4][5][6] Men are three to four times more likely to be affected than women, corresponding to 76-88% of patients, with a peak age of between 34 and 58 years. [7][8][9] Incidence of spine trauma and SCI varies around the world, with markedly different statistics between developing and non-developed countries. 10,11 In Asia Pacific, Taiwan has the highest rate , with 40.2 patients per million people with spine trauma, 12 followed by China and Saudi Arabia, which have rates of 23.7 and 38 patients per million people, respectively.…”
Section: Introductionmentioning
confidence: 99%